New frontiers in archaeology : proceedings of the Cambridge Annual Student Archaeology Conference 2019 - Kaercher, Kyra (Access archaeology., 2020)
The theme for the Cambridge Annual Student Archaeology Conference (CASA) 2019 was New Frontiers in Archaeology and this volume presents papers from a wide range of topics such as new geographical areas of research, using museum collections and legacy data, new ways to teach archaeology and new scientific or theoretic paradigms.